If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7a + 15) = 0 Reorder the terms: (15 + 7a) = 0 Remove parenthesis around (15 + 7a) 15 + 7a = 0 Solving 15 + 7a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 7a = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 7a = 0 + -15 7a = 0 + -15 Combine like terms: 0 + -15 = -15 7a = -15 Divide each side by '7'. a = -2.142857143 Simplifying a = -2.142857143
| 2x+8y=560 | | -4(y-2y)+7=-4(5y-y)+2+19y | | 4=4+5n+-4n | | -7v-2-4v=9 | | -4w-4(5z-6w)-6z= | | 12(3.14)2= | | (5x+8)+6=(8+5x)+6 | | (2x^2)(x+4)=0 | | 2645+476v= | | 11-5=-4 | | -3b+3b=6 | | 11d+10=6d-2 | | 3(d-8)-5=9 | | 4730-j=2712 | | 2.01=0.5*g*0.5 | | 3(-15)+8=2(-15)-7 | | 0=-16t^2+22t+3 | | logx+log(x-7)=log(18x) | | -52x+40x=27-9 | | 11m+13=m+30 | | 4(5y-7)-(7y+6)= | | 1.25=0.5*g*0.5 | | 3x-4=6x+1 | | -50x-(-90)=-54x-42 | | 5(8-6h)=h | | w-9.62=14.08 | | 5(2x+3)-4=2x+25 | | 4p^2=13p-3 | | 3x^2+5x=-10 | | y=0.5gt^2 | | -10=-10+77m | | -10(5x-9)=6(-9x-7) |